2015
DOI: 10.11606/issn.1806-6976.v11i3p129-135
|View full text |Cite
|
Sign up to set email alerts
|

Concepções dos usuários de crack sobre os fatores que influenciam o uso e a dependência

Abstract: Neste estudo objetivou-se identificar fatores influenciadores e facilitadores no uso do crack e os fatores que dificultam seu abandono. Trata-se de pesquisa qualitativa, envolvendo 20 usuários de crack, desenvolvida em João Pessoa, PB, em 2012. Os dados foram coletados através de formulário semiestruturado e analisados conforme a técnica do Discurso do Sujeito Coletivo. A facilidade de acesso, curiosidade, influência de pessoas e uso do álcool/maconha se mostraram fatores que influenciam o uso do crack e dific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…Thus, the study corroborates the results of a survey that has been carried out with crack users, in João Pessoa-PB, which demonstrates the use of drugs as a way of feeling pleasure, coping with conflicting situations, or even as a way of suppressing the desire to experience (11).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the study corroborates the results of a survey that has been carried out with crack users, in João Pessoa-PB, which demonstrates the use of drugs as a way of feeling pleasure, coping with conflicting situations, or even as a way of suppressing the desire to experience (11).…”
Section: Discussionsupporting
confidence: 86%
“…As the drug consumption becomes a conscious experience, a way of meeting the needs arising from physical, psychic and socio-economic impairments that modify the person's routine (11)(12)(13)(14)(15)(16)(17) , it can be seen as a reflected care (personal), as shown in the description: When the user becomes interested, it gets easier. When they recognize that they are users, that they need help, you have to talk, you have to dialogue, then it becomes easier (Yellow).…”
Section: Discussionmentioning
confidence: 99%
“…This result corroborates findings from the national research on crack cocaine, which showed that 78.9% of crack cocaine users reported a will to undergo treatment 11 . This can be related to the perception of the health and social hazards associated with crack cocaine use and the fear of harming family relations 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Somado a todos esses conflitos comuns à fase adolescente, alguns jovens têm seu desenvolvimento marcado pelo uso e abuso de álcool e outras drogas, que tornam a passagem pela adolescência ainda mais conflituosa. Alguns pesquisadores apontam que o consumo de drogas ilícitas se constitui em uma prática responsável pela ocorrência de vários prejuízos físicos, psíquicos e socioeconômicos (Rocha et al, 2015), com agravo ainda maior quando consumido mais precocemente, em virtude do processo de desenvolvimento a qual o indivíduo ainda está atravessando (Mari & Kieling, 2013). Além desses fatores, o período da adolescência, de acordo com Tavares (et al, 2001), representa uma etapa na qual há uma maior probabilidade de ocorrer experimentação de drogas, sejam elas lícitas ou ilícitas e embora na maioria das vezes esse uso seja apenas experimental, é possível notar comportamentos que refletem padrões de uso na vida adulta.…”
Section: Introductionunclassified